Challenges of Incorporating Sustainable Development Goals Into South African Higher Education Curricula - Nyika, Farai (Papanda Publishier, 2024)
This paper highlights several challenges that the adoption and implementation of the seventeen United Nations Sustainable Development Goals (SDGs) pose for South African Higher Education institutions’ (HEIs) curricula design. It also reflects on the experiences of some institutions who have embraced SDGs in their teaching and learning, research, management (governance and operations), and public engagement strategies (Sustainable Development Solutions Network, 2017). SD4 seeks to “ensure inclusive and equitable quality education and promote lifelong learning opportunities for all”. This paper is intended to contribute to policy debates on issues that are seemingly being given little attention in curriculum design, in the advance towards the target 2030 date for achieving SDGs. The research is motivated by the absence of guidelines and frameworks from South African education governing bodies regarding SDGs, leading to knowledge and capacity gaps that frustrate academics who are increasingly being required to include SDGs in their courses. The author uses a qualitative methodology (document review) and focuses on literature published between 2019 and 2023 on the implementation of SDGs into South African curricula. This study recommends that private HEIs be included in the development of SDG governing frameworks and policies. It also recommends that HEIs develop a South African ranking system to track progress towards SDG attainment.